Ambivalent sexism in the United Arab Emirates: Quantifying gender attitudes in a rapidly modernizing society. (August 2018) - Maitner, Angela T.; Henry, P. J.
The United Arab Emirates (UAE) has prioritized increasing equality between men and women. This research investigates whether equality initiatives are reflected in residents' attitudes toward women. Five hundred eighty-four Arab participants completed measures of ambivalent sexism, religiosity, and political conservatism, and reported stereotypes about women. Results suggest that Arab participants score similarly on measures of hostile and benevolent sexism to participants from other countries high in economic and political gender inequality; and measures of hostility and benevolence correlate with social attitudes as they do elsewhere around the globe. However, unlike in other datasets exploring contexts of high gender inequality, Arab women score significantly lower on benevolent sexism than men. We explore these findings in light of political and legal policies that have different implications for women's empowerment in the public and private spheres.